Game Edukasi Anak-Anak Tk Untuk Pengenalan Dasar Warna Dan Bentuk Berbasis Android Studi Kasus Tk Al Ulya - Alamsyah (Jurnal Komputer dan Informatika, 2024)
Learning media is a tool to help teachers convey information in learning activities, but currently there are still many early childhood education that carry out learning activities only using props and objects around them, students will be more interested in games that are easy to play and in them there are bright colors and animated images that attract attention and at this stage students will find it easier to remember a form of fruit or writing that has the characteristics of attractive colors and communicative and fun forms, based on the description above, it is important to create a learning media in the form of an educational game to introduce types of fruits, colors and others that can facilitate the learning process of students with the concept of learning at home or while playing